Дія та дійснІсть нормативності права (за Г. Кельзеном) - Заморська, Любов Ігорівна; Заморская, Любовь Игоревна; Zamorskaja, Ljubov' (My University, 2012)
In the article opens up maintenance of action and his correlation with effectiveness and reality of normativeness of law, the location of positive norm is determined as a fundamental category of law and his normativeness, and also maintenance of studies of G. Kel’zena about reality of normativeness of positive law.
Заморська Л. І. Дія та дійснІсть нормативності права (за Г. Кельзеном) / Л. І. Заморська // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 282-288.
Keywords: норма права; нормативність права; сфера дії норм позитивного права; дійсність права; нормативность права; сфера действия норм позитивного права; действительность права; law norm’s; normativeness of law; sphere of action of norms of positive law; reality of law